Stefan Dorn
Stefan Dorn

Reputation: 599

How to write a monad instance for a pair where both arguments have the same type?

Suppose I have a type Pair:

data Pair a = Pair a a

What is the right way to write a monad instance for it? My idea is roughly this:

instance Semigroup a => Semigroup (Pair a) where
  Pair a1 a2 <> Pair b1 b2 = Pair (a1 <> b1)(a2 <> b2)

instance Monad Pair where
  return = pure
  (Pair a b) >>= f = f a <> f b

Is it correct? If so then where to specify that b-type in the Pair b is a semigroup?

Upvotes: 9

Views: 1223

Answers (5)

Enlico
Enlico

Reputation: 28366

Why I am answering

I was curious to know what the practical usages of the Pair a monad are, especially considering that the only valid implementation of (>>=) actually throws away half of the data, so I asked this question.

It turns out that the answer I accepted is a very interesting answer to this question too (and was contained in Daniel Wagner's comment under the present question, but I hadn't noticed it), so I will elaborate it a bit here, because I've learned a lot from it.

The short answer: (a,a) and Bool -> a are the same thing

So the short answer is that the types Pair a, or more simply (a,a), and Bool -> a are isomorphic: feeding a (a,a) to fst/snd is equivalent to feeding a Bool -> a function with True/False (or False/True, it's just a choice). The two isomorphisms are actually shown in the (deleted) answer from Zhiltsoff Igor:

funToPair :: (Bool -> a) -> (a, a)
funToPair f = (f True, f False)

pairToFun :: (a, a) -> Bool -> a
pairToFun (x, y) True = x
pairToFun (x, y) False = y

As a consquence, whichever way Bool -> a is a monad, (a,a)/Pair a is a monad in the same way.

But (a,a)'s Monad throws information away... so does Bool -> a!

What bugged me at this point was that it's so apparent that the Monad instance for (a,a)/Pair a, thoroughly explained in Aadit M Shah's answer, throws away data, whereas the Monad instance for Bool -> a... doesn't...?

Fatally wrong! The Monad instance for r -> a (with generic r, not just Bool) throws away information all the time! How? Let's look at the well known implementation of >>=:

instance Monad ((->) r) where
    f >>= k = \ r -> k (f r) r

Now remember that a function of type x -> y is equivalent to a tuple of type (y,y,...,y) with as many entries as the number of possible values of type x (not y).

What about k? k is a binary function, let's say of type x -> y -> z, so it can be fed with the cartesian product of the values that inhabit the type x and those that inhabit the type of y. If x and y are inhabited by m and n values respectively, then k is equivalent to a tuple of type (z,z,...,z) with as many entries as m*n, and that is the information that comes with k.

Now the question is whether (>>=) makes use of all that information. No, it doesn't! (>>=) is feeding k with only n possible inputs: the second argument r is any value of type x, whereas the first argument is the single value corresponding to r via f.

If we think of mathematical functions, we are saying that, for fixed unary function f: A → B and binary function k: B×A → C, f >>= k is the unary function that does t ∈ A → k(f(t),t) ∈ C, i.e. it's a restriction of k to the curve parametrized by the equations x = f(t) and y = t.

Going back to Bool -> a, the signature of (>>=) specilizes to

(>>=) :: (Bool -> a) -> (a -> Bool -> b) -> Bool -> b
f >>= k = \r -> k (f r) r

which we can rewrite as follows, just to make the obvious more apparent:

(>>=) f k r
  | r == True  = k (f True)  True
  | r == False = k (f False) False
-- remember this

What's obvious in the above? If we feed f >>= k with True, we'll only use f True, thus throwing away the other half of the data, f False. Similarly, if we call (f >>= k) False, we throw away whatever f True is. This way of throwing away half of the information contained in k mirrors exactly what is throw away via the _ placeholders for (a,a) aka Pair a (adaptation from Ismor's answer):

instance Monad Pair where 
  return = pure
  (Pair a b) >>= k = let Pair a' _  = k a
                         Pair _  b' = k b
                     in  Pair a' b'

Indeed, if we define fst' (Pair a _) = a and snd' (Pair _ b) = b (these are mirroring fst and snd for (,)), then (>>=) can be written simply as follows

(>>=) :: Pair a -> (a -> Pair b) -> Pair b
p >>= k = (fst' (k (fst' p)),
           snd' (k (snd' p)))

Which is in my opinion strikingly similar to the code I marked with -- remember this, with fst' mirrors True and snd' mirrors False.

By the way, for the following, let's take note of the type of (>>=) in the case we were allowed to write it for (a,a):

(>>=) :: (a,a) -> (a -> (b,b)) -> (b,b)

What about (a,b) when a and b are the same type?

This was the last doubt I had: since (a,b) is a Monad in b provided a is a Monoid, in the special case that the type b is equal to the type a (and b has to be a Monoid), do we get the same instance as above?

No, the question above is ill-posed, the flaw being in the part "in the special case that the type b is equal to the type a". This hypothesis is simply not possible because for a type constructor to be a Monad, it has to have one and only one free type parameter:

  • (a,b) is made a Monad in the free parameter b, meaning that b will be allowed to vary according to the second argument to (>>=), whereas the type a will stay the same through the (>>=) operator;
  • (a,a) is made a Monad in the free parameter a, meaning that a will be allowed to vary according to the second argument to (>>=), whereas... nothing, that's it, all explained in the previous part of the answer.

Upvotes: 0

Aadit M Shah
Aadit M Shah

Reputation: 74204

Actually, the only correct monad instance of Pair is as follows.

instance Monad Pair where
    m >>= f = joinPair (f <$> m)

joinPair :: Pair (Pair a) -> Pair a
joinPair (Pair (Pair x _) (Pair _ y)) = Pair x y

The reason this is the correct monad instance is because Pair is a representable functor.

instance Representable Pair where
    type Rep Pair = Bool

    index (Pair x _) False = x
    index (Pair _ y) True  = y

    tabulate f = Pair (f False) (f True)

Turns out, for every representable functor (>>=) is equivalent to the following bindRep function.

bindRep :: Representable f => f a -> (a -> f b) -> f b
bindRep m f = tabulate (\a -> index (f (index m a)) a)

If we specialize the bindRep function to Pair we get the following.

bindRep :: Pair a -> (a -> Pair b) -> Pair b
bindRep (Pair x y) f = tabulate (\a -> index (f (index (Pair x y) a)) a)
                     = Pair (index (f x) False) (index (f y) True)
--                          |_________________| |________________|
--                                   |                   |
--                           (1st elem of f x)   (2nd elem of f y)

The following blog post by Adelbert Chang explains it better. Reasoning with representable functors.


Here's another way to prove uniqueness. Consider the left and right identity monad instance laws.

return a >>= k = k a -- left identity law

m >>= return = m     -- right identity law

Now, for the Pair data type return x = Pair x x. Hence, we can specialize these laws.

Pair a a >>= k = k a     -- left identity law

m >>= \x -> Pair x x = m -- right identity law

So, what should the definition of >>= be in order to satisfy these two laws?

Pair x y >>= f = Pair (oneOf [x1, x2, y1, y2]) (oneOf [x1, x2, y1, y2])
    where Pair x1 y1 = f x
          Pair x2 y2 = f y

The oneOf function returns one of the elements of the list non-deterministically.

Now, if our >>= function is to satisfy the left identity law then when x = y then x1 = x2 and y1 = y2 and the result must be Pair (oneOf [x1, x2]) (oneOf [y1, y2]).

Similarly, if our >>= function is to satisfy the right identity law then x1 = y1 = x and x2 = y2 = y and the result must be Pair (oneOf [x1, y1]) (oneOf [x2, y2]).

Hence, if you want to satisfy both laws then the only valid result is Pair x1 y2.

Upvotes: 15

lsmor
lsmor

Reputation: 5063

Functor and applicative instances are easy. The monad instance has taken a while to me.

data Pair a = Pair a a deriving (Eq, Show)

instance Functor Pair where 
  fmap f (Pair a b) = Pair (f a) (f b)

instance Applicative Pair where 
  pure a = Pair a a
  (Pair f g) <*> (Pair a b) = Pair (f a) (g b)

instance Monad Pair where 
  return = pure
  (Pair a b) >>= f = let Pair a' _ = f a 
                         Pair _ b' = f b
                     in  Pair a' b'

The way I've come to this solution is by applying the monad laws. Easily you can check with an example that identity law doesn't hold if you take Pair a' a'' or Pair b' b'' or Pair a' b' nor Pair a'' b''. So the only solutions must be in the diagonals. Defining

(m >>= f) = Pair (first . f . first $ m) (second . f . second $ m)

where first and second are the obvious ones, you can proof all of the laws.

Upvotes: 4

n. m. could be an AI
n. m. could be an AI

Reputation: 119847

It is possible to make Pair into Monad by having join that takes the diagonal.of the 2×2 square. return has no other choice but replicate its argument. This turns Pair into essentially a fixed length ZipList.

Of course this definition of join discards some data. This may or may not be important.

Upvotes: 3

amalloy
amalloy

Reputation: 91837

A Monad instance may not place any constraints on the type of data it contains (the a here). It must treat that data as fully opaque. I don't think your Pair type admits a Monad instance (or Applicative), because there is no way to turn a pair of pairs into a single pair without either losing some of the data, or using it in some way not permitted by the typeclass definition.

Upvotes: 0

Related Questions